Clustering companies listed on the Warsaw Stock Exchange according to time-varying beta - Szczepocki, Piotr (Grupowanie spółek notowanych na Giełdzie Papierów Wartościowych w Warszawie według bet zmiennych w czasie, 2019)
The beta parameter is a popular tool for the evaluation of portfolio performance. The Sharpe single-index model is a simple regression model in which the stock’s returns are regressed against the returns of a broader index. The beta parameter is a measure of the strength of this relation. Extensive recent research has proved that the beta is not constant in time and should be modelled as a time-variant coefficient. One of the most popular methods of the estimation of a time-varying beta is the Kalman filter. As the output of the Kalman filter, one obtains a sequence of the estimates of a time-varying beta. This sequence shows the historical dynamics of sensitivity of a company’s returns to the variations of market returns. The article proposes a method of clustering companies listed on the Warsaw Stock Exchange according to time-varying betas
Econometrics = Ekonometria, 2019, Vol. 23, No. 2, s. 63-79
Keywords: time series clustering; cluster analysis; time-varying beta; grupowanie szeregów czasowych; analiza skupień; bety zmienne w czasie; CAPM